Analisis Tekno-Ekonomi Produksi Pupuk Cair Ramah Lingkungan dari Limbah Air Budidaya Ikan Berbasis Masyarakat - Nizar Amir; Hakam Muzakki; Hoomzah Nur Alisiyah; Raden Apriyanto (Universitas Trunojoyo Madura, 2022)
There are two important aspects of the implementation of this research, namely the technical aspect, which includes the production and analysis of the quality of liquid fertilizer products from fish farming wastewater, and the economic aspect, which includes an economic analysis on an industrial scale. Liquid fertilizer is made from fish farming wastewater obtained from Bangkalan Regency, East Java Province, Indonesia. The process of producing liquid fertilizer from fish farming wastewater includes various processes, from mixing to fermentation. The physical characteristics of liquid fertilizer from fish farming wastewater are in accordance with existing standards. Without the addition of nutrients, liquid fertilizer from fish farming wastewater has nitrogen (N) 1.33%, phosphorus (P) 0.44%, and potassium (K) 0.38%. Although the nutrient content of liquid fertilizer from fish farming wastewater is still below the standard of SNI 02-4958-2006, in industrial-scale production processes, adding nutrients is very necessary. In the economic analysis, all economic parameters are declared feasible and profitable, with an NPV value of Rp. 5,524,899,840, IRR 31,79%, PP 3.15 years and B/C ratio 3.1. This study shows a positive value on the technical and economic aspects. Finally, this research can be used as a reference by academics, government, and entrepreneurs in the technical and economic aspects of producing liquid fertilizer from fish farming wastewater.